REUSABILITY IN THE DEVELOPMENT OF A WEB SYSTEM USING THE ANGULAR FRAMEWORK - Bagliotti, Ian Rotondo; Gibertoni, Daniela (Revista Interface Tecnológica, 2020)
On the world stage, software development has considerably increased its demand with a focus on solving, optimizing problems or market opportunities, guarantee product quality, customer satisfaction and add value to the business, requiring short deadlines and delivery times being required increasingly short. In the midst of the vast competition for improvements and agile deliveries, mechanisms and technologies emerge to increase productivity in coding, facilitate maintainability through reusability and provides a basis to start implementation through frameworks. This article addresses, through exploratory and experimental bibliographic research, the techniques of code reuse, from which a web system was developed for a philanthropic entity using the framework front-end Angular e Node.js on back-end, with the purpose of investigating and identifying the main characteristics of reusability in this case study. The main results obtained are the search for optimization in the creation process and maintainability, through reusability practices and Angular functionalities.